Efektifitas Penerapan Alternative Dispute Resolution (Adr) Pada Penyelesaian Sengketa Bisnis Asuransi Di Indonesia - Purwanto (Fakultas Hukum Universitas Mulawarman, 2005)
Requirement of protection for risks which possible befall human being and good and chattel which owning of, representing stimulan for growth and eksistence of insurance business. In its growth of insurance business in Indonesia, accompanied also with amount and dispute quality between insurance company with client. Solving of inveterate business dispute through band litigasi, in its growth looked into less be effective since process of solving which have the ladder, start from Pengadilan Negeri to Mahkamah Agung, if among the parties there is disgruntled with previous justice decision. The forces of UU No.30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa (Arbitrase and Alternative Dispute Resolution), representing a strategic step in area of regulasi law which is gone through by government in the effort giving alternative to society to finish their business dispute off the court. The implementation of Alternative Dispute Resolution ( ADR), looked into effective enough in order to realizing satisfaction to all party which have dispute, since process and reached agreement represent will;desire with from the parties. Beside that, time efficiency, expense, energy and mind, and also secret more well guaranted the parties. This phenomenon will have an in with belief storey level socialize to insurance company, what in the end affect positive for growth and eksistence of insurance business. Key words : insurance (asuransi) , business (bisnis), disputes (sengketa) , the parties (para pihak), alternative dispute resolution (alternatif penyelesaian sengketa).